2017
DOI: 10.1080/0284186x.2016.1266084
|View full text |Cite
|
Sign up to set email alerts
|

The cost of survival: an exploration of colorectal cancer survivors’ experiences of pain

Abstract: Background: The Institute of Medicine report 'From Cancer Patient to Cancer Survivor' has drawn widespread attention to the experiences of cancer survivors. Research examining the symptom experiences of survivors are proliferative within the literature but limited by samples which include multiple tumor groups and varying inclusion criteria. This cross-sectional quantitative study seeks to examine pain and quality of life (QoL) in the context of colorectal cancer (CRC) survivorship, as defined by the Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
11
0
3
Order By: Relevance
“…42 This result indicated that people with higher levels of education were more conscious of their health, which, in turn, led to less exposure to environmental risk factors, frequent health checkups, and a reduced likelihood of advancement to later cancer stages. 43,44 Furthermore, being younger was recognized as a predictor of poorer HRQoL scores, a finding that was in line with recent studies on other types of cancers; specifically, one study on CRC survivors' pain in the UK 45 and another in Australia. 46 In general, we believe this correlation may reflect patients' life-stage expectations and demands.…”
supporting
confidence: 79%
“…42 This result indicated that people with higher levels of education were more conscious of their health, which, in turn, led to less exposure to environmental risk factors, frequent health checkups, and a reduced likelihood of advancement to later cancer stages. 43,44 Furthermore, being younger was recognized as a predictor of poorer HRQoL scores, a finding that was in line with recent studies on other types of cancers; specifically, one study on CRC survivors' pain in the UK 45 and another in Australia. 46 In general, we believe this correlation may reflect patients' life-stage expectations and demands.…”
supporting
confidence: 79%
“…The prevalence of sleep disturbance and depression in people living with cancer is 40.0%–85.1% and 9.0%–38.2%, respectively (Fortmann et al., 2018; Krebber et al., 2014; Li et al., 2017; Tsaras et al., 2018). Physical, cognitive, and psycho‐emotional symptoms may persist for months post‐treatment (Shi et al., 2011; Vardy et al., 2016), and have been found to greatly interfere with productivity, negatively impacting the quality of life in people living with cancer (Day & Thorn, 2010; Drury et al., 2017). Factors associated with severe symptom phenotype are complex and include age, educational level, cancer type and stage, and sedentary lifestyle (Tsaras et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CRC has demonstrated an increasing incidence in recent years (2). For patients with CRC, postoperative ostomy care is difficult and gastrointestinal function is impaired, resulting in a lower quality of life and increasing the extent of pain during subsequent radiotherapy and chemotherapy (5,6). Therefore, investigating new therapeutic methods for treating CRC, new effective compounds and novel signaling pathways have become areas of focus for research in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, following surgery, patients often have reduced gastrointestinal function, reduced immunity and also require cumbersome nursing care (5). As a result, the pain caused by subsequent radiotherapy and chemotherapy also increases (6). Therefore, targeted drugs play an important role in the treatment of CRC (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%